A case report of quadriplegia in tubercular meningitis - Jain, Archita; Agrawal, Dhruv (International Journal of Contemporary Pediatrics, 2025)
Twenty-five percent of the paediatric tubercular cases are extrapulmonary, with tubercular meningitis being the most common cause of death because of TB. Quadriplegia is relatively uncommon but serious complication of tubercular meningitis and is a marker of poor prognosis. The delay in diagnosing and adequately treating this condition is associated with significant morbidity and mortality. A 10-year-old male patient, came with complaint of fever since, 1 month and progressive weakness of all 4 limbs since, 20 days and Impaired consciousness since, 10 days. Investigations were sent and the MRI and CSF findings were conclusive of tuberculous meningitis. He was started on Anti tubercular drugs and steroids. The patient conditioned improved gradually, his truncal and limb tone and motor function improved, he started responding to stimuli, was able to walk and speak. Tuberculous meningitis is one of the most severe and lethal forms of tuberculous infection and delayed onset of the treatment due to non-specific early signs and symptoms might be fatal. TBM in children can cause different neurologic sequalae’s like quadriplegia, cranial nerve palsies or even death, thus early onset of the treatment is of paramount importance and life-saving.